2001
DOI: 10.5962/bhl.part.80166
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and phenology of Schizomida (Arachnida) from a secondary upland forest in Central Amazonia

Abstract: Abundance and phenology of Schizomida (Arachnida) from a secondary upland forest in Central Amazonia. -The 357 Schizomida (shorttailed whipscorpions) collected within 12 months from the soil (0-7 cm depth) of a secondary upland forest (60.4 + 32.2 ind./m?/month) near Manaus are represented by the hubbardiids Surazomus mirim and S. rodriguesi (99.7% and 0.3% of the total catch, respectively). About 74% of all specimens of S. mirim inhabited the organic soil layer (0-3.5 cm depth) where monthly catches of juveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Vasconcellos (2003) studied termites in several areas of Atlantic Forest of Northeastern Brazil (Mata do Buraquinho included) and observed that the abundance can change accordingly to the climatic differences throughout the year, but the richness remains the same, independent of the season of the year. Adis et al (1989Adis et al ( , 1999 did not observe differences in abundance of Ricinulei and Schizomida in rainy forests. Xavier and Rocha (2001) and Martins et al (2004) observed differences in abundance of Solifugae in open forest formations (Caatinga and Cerrado).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Vasconcellos (2003) studied termites in several areas of Atlantic Forest of Northeastern Brazil (Mata do Buraquinho included) and observed that the abundance can change accordingly to the climatic differences throughout the year, but the richness remains the same, independent of the season of the year. Adis et al (1989Adis et al ( , 1999 did not observe differences in abundance of Ricinulei and Schizomida in rainy forests. Xavier and Rocha (2001) and Martins et al (2004) observed differences in abundance of Solifugae in open forest formations (Caatinga and Cerrado).…”
Section: Discussionmentioning
confidence: 92%
“…There is no available literature to verify spider seasonality in urban habitats. However, other papers deal with the influence of the seasons of the year on the spider fauna associated with different forest habitats (Adis et al 1989;Nentwig 1993;Adis et al 1999;Xavier and Rocha 2001;Martins et al 2004). There are probably two seasonality patterns for spider communities: the richness never changes despite the forest type and the abundance changes according to the forest formation.…”
Section: Discussionmentioning
confidence: 97%
“…The "endemism hypotheses" to the Ananteris group of the Northeastern will have to be revised. ADIS et al (1999) recorded that the total catches of specimens of a species of Schizomida in the Central Amazonia during dry and rainy season is the same. MARTINS et al (2004) showed that one species of Solifugae in the open forest has two activity peaks during the year: the highest peak occurred in the dry season and the lowest in the wet season.…”
Section: Discussionmentioning
confidence: 99%
“…All specimens studied were captured with Winkler apparatus in primary upland Amazonian Rain forest (Terra Firme). The sex ratio observed was 1:1, the same as observed for the Peruvian Surazomus chavin (see PINTO-DA-ROCHA 1996), and contrasting with the Central Amazonian species S. brasiliensis in which more females were found (ADIS et al 1999).…”
mentioning
confidence: 60%